THE SHADOW IN THE LIBRARY: FAIR DEALING, DIGITAL ENTICEMENT, AND THE BLURRING LINE BETWEEN INFRINGEMENT AND PLAGIARISM IN NIGERIA - Eigbemekhe, Michael E.; Nwocha, Mathew E.; Amah, Emmanuel I. (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The advent of the digital era and information age has opened a floodgate for access to information for research purposes and private study. This phenomenon has also increased the rate at which researchers are able to copy other author’s works and abuse the privilege of the fair dealing doctrine provided in section 20(1) of the Nigerian Copyright Act (NCA) 2022. Using the doctrinal approach, this paper examined how the abuses of the fair dealing doctrine has resulted in the twin vices of copyright infringement and plagiarism. The paper examined the differences between copyright infringement and plagiarism, and whether they coalesce under the NCA 2022. It was found that by requiring ‘acknowledgement’ or attribution of copyrighted works for the application of the fair dealing doctrine under section 20(1) of the NCA 2022, the new Act has effectively merged both copyright infringement and plagiarism under our law, especially in view of the enforceability of moral rights under section 14 of the Act.